AKULTURASI SISTEM KEWARISAN: PENYELESAIAN SENGKETA PUSAKA TINGGI DI MINANGKABAU (Lex Jurnalica, 2017)
AbstractThe law of inheritance according to Minangkabau adat law is always an actual problem in various discussions. It may be due to its uniqueness when compared to the customary legal system of inheritance from other regions in Indonesia. The polemic of Islamic inheritance law which may also be somewhat intriguing is the question of its exposure to customary law. It is this fact that led to the theory that in fact the Minangkabau Indigenous people after the entry of Islam until now not only apply one system of inheritance just as long as it is in taxable, but there is dualism of the System of Inheritance in the implementation of its inheritance, namely: First, the system of inherited Collective-Matrilinial Inheritance on the Heritage Treasure; and, Second, the Individual-Bilateral Inheritance System imposed on the Low Treasure. Based on this background then that will be discussed in this writing about: Is the application of inheritance in accordance with the principles of Islamic heritage? And How to resolve the disputes of high treasures in Minangkabau society? Associated with the legal issues of inheritance, one of which is in Pariaman regency, the area located on the coast of the island of Sumatra, is currently very heterogeneous. Although still using matrilineal kinship system but in the current development no doubt there has been a shift in the application of inheritance law. Keywords: heritage treasure, low treasure, minangkabau traditional system AbstrakHukum waris menurut hukum adat Minangkabau senantiasa merupakan masalah yang aktual dalam berbagai pembahasan. Hal itu mungkin disebabkan karena keunikannya bila dibandingkan dengan sistem hukum adat waris dari daerah-daerah lain di Indonesia ini. Polemik hukum waris Islam yang mungkin juga agak menggelitik adalah persoalan mengenai persentuhannya dengan hukum adat. Kenyataan inilah yang memunculkan teori bahwa sebenarnya masyarakat Adat Minangkabau setelah masuknya agama Islam hingga saat ini tidak hanya menerapkan satu sistem kewarisan saja seperti selama ini di kenaI, tetapi terdapat dualisme Sistem Kewarisan dalam pelaksanaan warisnya, yaitu: Pertama, Sistem Kewarisan Kolektif-Matrilinial yang diberlakukan pada Harta Pusaka Tinggi; dan, Kedua, Sistem Kewarisan Individual-Bilateral yang diberlakukan pada Harta Pusaka Rendah. Berdasarkan latar belakang tersebut maka yang akan dibahas dalam penulisan ini mengenai: Apakah penerapan harta pusaka sesuai dengan prinsip kewarisan Islam? Dan Bagaimana penyelesaian sengketa harta pusaka tinggi di masyarakat minangkabau? Terkait dengan permasalahan hukum waris tersebut, salah satunya ada di Kabupaten Pariaman, daerah yang terletak di pesisir pantai pulau Sumatera ini, saat ini sangatlah heterogen. Walaupun masih menggunakan sistem kekerabatan matrilineal tetapi dalam perkembangan saat ini tidak dipungkiri lagi telah terjadi pergeseran dalam penerapan hukum warisnya. Kata kunci: harta pusaka tinggi, harta pusaka rendah, sistem adat minangkabau